2019
DOI: 10.1021/acsmacrolett.9b00221
|View full text |Cite
|
Sign up to set email alerts
|

Glyco-Platelets with Controlled Morphologies via Crystallization-Driven Self-Assembly and Their Shape-Dependent Interplay with Macrophages

Abstract: Two-dimensional (2D) materials are of great significance to the materials community for their high surface area and controllable surface properties. However, controlled preparation of 2D structures with biological functions and biodegradable features is considerably hard. In this work, we demonstrate that, by careful selection of building block structures and assembly conditions, the above obstacle can be overcome partially by crystallization-driven self-assembly (CDSA) from PLLA-based diblock glycopolymers. 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
88
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(92 citation statements)
references
References 40 publications
4
88
0
Order By: Relevance
“…This has now been achieved for a variety of crystallizable core-forming blocks, such as PFDMS, 250,253,254 polycarbonate, 62 PDHF, 251 PCL, 169,255 PLLA, 252,[256][257][258] , PE, 70,72 OPV. 259 Watersoluble low dispersity triblock fiber-like comicelles with a PFDMS core have also been prepared by living CDSA.…”
Section: Nanomedicinementioning
confidence: 99%
See 1 more Smart Citation
“…This has now been achieved for a variety of crystallizable core-forming blocks, such as PFDMS, 250,253,254 polycarbonate, 62 PDHF, 251 PCL, 169,255 PLLA, 252,[256][257][258] , PE, 70,72 OPV. 259 Watersoluble low dispersity triblock fiber-like comicelles with a PFDMS core have also been prepared by living CDSA.…”
Section: Nanomedicinementioning
confidence: 99%
“…255 In 2017, living CDSA was achieved in water for the first time with a PCL-based triblock terpolymer. 169 256 The size of 2D platelets comprising PLLA-b-PDMAEMA (PDMAEMA = poly(dimethylaminoethyl methacrylate)) with coronal quaternization has also been found to affect their inhibition of bacterial growth. 257 A detailed study found that small platelets have higher antibacterial activity compared to large platelets or spherical particles.…”
Section: Nanomedicinementioning
confidence: 99%
“…In 1966, Lotz et al first found that poly(ethylene glycol)- b -polystyrene (PEO- b -PS) block copolymers (BCP) could form square-shaped platelets through crystallization from ethyl benzene solutions [ 5 ]. Since then, the preparation of micelles from crystalline-coil BCPs by crystallization-driven self-assembly (CDSA) has been gaining momentum [ 4 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cylinders and lamellar architectures are the most commonly observed morphologies [ 8 , 14 , 15 , 16 ]. However, modifying the interactions between the two blocks and the solvent, and the interplay between the crystallization of the core-forming block and the corona chain stretching, gives access to more complex structures that may incorporate desired properties [ 13 , 17 , 18 , 19 ]. In solvents able to solubilize both blocks, the BCP remains as unimers undergoing a slower crystallization process and can form larger defect-free crystals (platelets, for example) [ 13 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation